Comparison of Some Modern IT Equipment as Detectors for Microfluidic Paper-based Determination of Phosphate - Wasin Wongwilai (Science Faculty of Chiang Mai University, 2019)
Modern Information Technology (IT) and communications equipment (mobiles phones, scanners, etc) may all be used as image capture devices for paper-based colorimetric analysis. This paper evaluates the use of a mobile phone, a webcam, a flatbed scanner and a handheld scanner as image capture devices for colorimetric determination of reactive phosphate using microfluidic paper-based analytical devices as the analytical platform. All four image capture devices tested gave similar analytical sensitivity and limits of detection (0.5-0.6 mg L-1 as P), although the handheld scanner and webcam exhibited non-linear responses over the range of concentrations tested, making them less suitable for field applications. The repeatability of the two scanners (<14% RSD) was superior to that of the mobile phone and webcam (ca 25% RSD). The flatbed scanner gave the best overall analytical performance.